Efficacy of a long‐lasting bifenthrin‐treated net against horticultural pests and its compatibility with the predatory mite Amblyseius swirskii and the parasitic wasp Eretmocerus mundus. Issue 8 (8th February 2017) - Fernández, Maria del Mar; Colomer, Ignacio; Medina, Pilar; Fereres, Alberto; Del Estal, Pedro; Viñuela, Elisa
Abstract: BACKGROUND: Insecticide‐treated nets (ITNs) have been investigated recently for their use in agriculture. Depending on the insecticide, the hole size and the way they are produced, these nets can target different pests and therefore they could be interesting options for use in integrated pest management (IPM). As the information on their compatibility with beneficial fauna is practically negligible, in this work we have tested the compatibility of an experimental bifenthrin long‐lasting insecticide‐treated net (LLITN) with Amblyseius swirskii and Eretmocerus mundus, important natural enemies of whiteflies and thrips, under laboratory, semi‐field and commercial greenhouse conditions. RESULTS: In the laboratory, the treated net was very deleterious to adults of both natural enemies, after 72 h exposure. However, in choice tests with Y‐tubes, both natural enemies were neither attracted nor repelled by the treated net and no short‐term mortality was detected in individuals that had crossed it. No deleterious effects on the E. mundus beneficial capacity were detected in semi‐field trials. In field trials, the LLITN proved to be compatible with A. swirskii while decreasing pest densities. CONCLUSIONS: Bifenthrin LLITN studied could be a valuable method for reducing pest population infestations in IPM programmes while being compatible with biocontrol agents. © 2017 Society of Chemical Industry